Combined use of field observations and SAR interferometry to study ice dynamics and mass balance in Dronning Maud Land, Antarctica - Dietrich, Reinhard; Metzig, Robert; Korth, Wilfried; Perlt, James (Polar Research, 1999)
In the region of the Schirmacheroase (71 °S, 12°E) various geodetic and glaciological research activities have been carried out in the last decade. Several times three geodetic-glaciological traverses were undertaken to study ice velocity, accumulation and ablation, and ice surface height changes. Repeated ground surveys show a significant decrease in surface heights by about 15 cm/y for a large blue-ice area. This paper presents the first interferometrically derived ice velocity field of the inland ice close to the Schirmacheroase. The interferometric analysis of the synthetic aperture radar (SAR) data is performed in combination with ground-based information. Since only ERS-1&2 tandem mission image couples are available for this region a digital elevation model (DEM) is used to remove the effect of topography. Ice velocities up to 100 m/y are proved interferometrically for this part of the inland ice.
Keywords: Dronning Maud Land; geodesi; glasiologi; innlandsis

Predicted present-day evolution patterns of ice thickness and bedrock elevation over Greenland and Antarctica - Huybrechts, Philippe; Le Meur, Emmanuel (Polar Research, 1999)
This paper discusses predicted evolution patterns of present-day changes of ice thickness, surface elevation, and bedrock elevation over the Greenland and Antarctic continents. These were obtained from calculations with dynamic 3-D ice sheet models which were coupled to a visco-elastic solid Earth model. The experiments were initialized over the last two glacial cycles and subsequently averaged over the last 200 years to obtain the current evolution. The calculations indicate that the Antarctic Ice Sheet is still adjusting to the last glacial-interglacial transition yielding a decreasing ice volume and a rising bedrock elevation of the order of several centimetres per year. The Greenland Ice Sheet was found to be close to a stationary state with a mean thickness change of only a few millimetres per year, but the calculations revealed large spatial differences. Predicted patterns over Greenland are characterized by a small thickening over the ice sheet interior and a general thinning of the ablation area. In Antarctica, almost all of the predicted changes are concentrated in the West Antarctic Ice Sheet, which is still retreating at both the Weddell and Ross Sea margins. Over most of both ice sheets, the model indicates that the surface elevation trend is dominated by ice thickness changes rather than by bedrock elevation changes.
Keywords: Antarktis; glasiologi; innlandsis; polarområdene

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

EPICA Dronning Maud Land pre-site survey - Karlöf, Lars; Gjerde, Knut; Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; geodesi; innlandsis; topografi

Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

A study of the ice dynamics of Jutulstraumen drainage area, by means of remote sensing - Rolstad, Cecilie; Hagen, Jon Ove; Østen, Kristoffer; Tonning, Tore; Semb, Svein Ingar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Antarktis; NARE 1997/98; akkumulasjon; glasiologi; innlandsis; klimaendringer

Ice sheet history from Antarctic Continental Margin sediments: The ANTOSTRAT approach - Barker, Peter; Barrett, Peter; Camerlenghi, Angelo; Cooper, Alan; Davey, Frederick; Domack, Eugene; Escutia, Carlota; Kristoffersen, Yngve; O'Brien, Philip (Terra Antarctica, 1998)
Keywords: Antarktis; glasiologi; innlandsis; sedimentologi

Water masses in the southern Weddell Sea - Gammelsrød, Tor; Myking, Steinar; Nøst, Anders; Skagseth, Øystein; Østerhus, Svein (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; innlandsis; oseanografi; vannmasser

Convergent flow of ice within the Astrolabe subglacial basin, Terre Adélie, East Antarctica: an hypothesis derived from numerical modelling experiments - Siegert, Martin J; Glasser, Neil F (Polar Research, 1997)
Keywords: Antarktis; geologi; geomorfologi; glasiologi; innlandsis; subglasial innsjø

A stable isotope pilot study from blue ice areas at Jutulsessen, Dronning Maud Land, Antarctica - Thomsen, Henrik Højmark; Hagen, Jon Ove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; innlandsis; isbre; klimaendringer

Epica Dronning Maud Land pre site survey 1996/97 - Winther, Jan-Gunnar; Broeke van den, Michiel R.; Conrads, Louk; Eiken, Trond; Hurlen, Robert; Johnsrud, Georg; Karlöf, Lars; Onarheim, Stig; Richardson, Cecilia; Schorno, Raymond (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; akkumulasjon; innlandsis; is radar; meteorologi; snø radar; topografi